Effectiveness of Digital Game Based Learning Strategy in Higher Educational Perspectives - Bakhsh, Khuda; Hafeez, Muhammad; Shahzad, Shumaila; Naureen, Bushra; Farid, Muhammad Faisal (Journal of Education and e-Learning Research, 2022)
Digital game-based learning strategy is now widely used in various fields such as education, marketing and advertising. This learning strategy has attracted great attention from scholars and practitioners in recent years due to its effectiveness in various educational fields. As more research studies favored the constructive impact of games on the learning process, more and more investigators are dedicated to developing digital educational games to enhance learning skills for 21st century requirements. The objectives of the current investigation were: to present a comprehensive and systematic review of the literature of previous studies on the effectiveness of digital game-based learning strategy in a higher educational context; to report the role of various adult learning theories in digital game-based learning strategy; to highlight some barriers and their solutions in digital game-based learning strategy. A total of 20 previous studies on digital game-based learning strategy in higher educational perspectives published from 2008-2021 were selected by inclusion and exclusion criteria for conducting this investigation. The results of the current investigation revealed that digital game-based learning strategy has deep effects on the learning skills of the learners in higher educational perspectives. The digital game-based learning strategy is a better option for the improvement of engagement of learners towards learning and critical thinking skills.